2021
DOI: 10.1002/ptr.7010
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin promotes osteogenic differentiation and antioxidant responses of mouse bone mesenchymal stem cells through activation of the AMPK/SIRT1 signaling pathway

Abstract: Decrepitude and apoptosis of bone mesenchymal stem cells (BMSCs) induced by reactive oxygen species (ROS) lead to inhibited osteogenic differentiation, causing decreased bone density and osteoporosis. Quercetin, a bioactive component of Solanum muricatum extracts, promotes the osteogenic differentiation of BMSCs and ameliorates the symptoms of osteoporosis in vivo. However, the detailed mechanism underlying this process remains unclear. The study aims to reveal the regulatory mechanism of quercetin in BMSCs. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…Given the evidence (44) that immune responses are overactive at early stages and application of immunosuppressants at early stages significantly limits HO development, the dampened initial overactivation of macrophages by quercetin might also constitute an osteogenic-suppressive immune microenvironment that inhibits aberrant HO formation, which was indicated by diminished PDGFRa+ mesenchymal stem cell accumulation. As previous study also indicated that quercetin could dose-dependently promote osteogenic differentiation of stem cells (63)(64)(65), the inhibitory effects of quercetin on HO might primarily attribute to its immunomodulatory property.…”
Section: Discussionmentioning
confidence: 64%
“…Given the evidence (44) that immune responses are overactive at early stages and application of immunosuppressants at early stages significantly limits HO development, the dampened initial overactivation of macrophages by quercetin might also constitute an osteogenic-suppressive immune microenvironment that inhibits aberrant HO formation, which was indicated by diminished PDGFRa+ mesenchymal stem cell accumulation. As previous study also indicated that quercetin could dose-dependently promote osteogenic differentiation of stem cells (63)(64)(65), the inhibitory effects of quercetin on HO might primarily attribute to its immunomodulatory property.…”
Section: Discussionmentioning
confidence: 64%
“…Quercetin can heighten the BMSCs osteogenic differentiation and increase bone mineral density [6][7][8][9]. However, optimal concentration of quercetin treatment remains debatable.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin, a naturally available flavonoid and a wellknown phytoestrogen [5], exerts antioxidant and antiinflammatory properties. In vitro, quercetin promotes osteogenic differentiation of BMSCs via extracellular-signal-regulated protein kinases, adenosine 5'-monophosphate (AMP)-activated protein kinase/sirtuin 1, and estrogen receptor-mediated pathways [6][7][8]. In vivo, in rat models of postmenopausal osteoporosis, quercetin heightens BMSC osteogenic differentiation to increase the bone mineral density [9].…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin is one of the natural polyphenols, which widely exists in various plants and was consumed worldwide(18). It has multiple pharmacological effects reported by many studies, such as protecting the bone, reduceing blood glucose, blood pressure, and lipid, and immunomodulatory, anti-in ammatory, and antioxidation activities (19)(20)(21). Wogonin, a compound extracted from the Scutellaria baicalensis plant, exhibits high anti-in ammatory and antioxidative properties, which is achieved reduce expression of transforming growth factor β1 (TGF-β1), high temperature receptor A1 (HTRA1), matrix metalloprotease 13 (MMP-13) and nuclear factor kappa-lightchain-enhancer of activated B cells (NF-κB) (22,23).…”
Section: Discussionmentioning
confidence: 99%